Economic Liberalization And Its Link To Convergence: Empirical Evidence From Rcep and TPPA Countries - Rossazana, Ab. Rahim; Selvarajan, Sonia Kumari (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Economic liberalization has been the emphasis of adjustment policies in developing countries; ASEAN countries jumped on the bandwagon and espoused economic reforms by liberalizing its international trade and financial policies. Through the development of free trade agreement policies such as AEC and RCEP, regional economic integration is accelerating in South East Asia; not leaving behind the less developed member countries such as Cambodia, Lao PDR, Myanmar and Vietnam (CLMV). Hence, the objectives of this paper are to examine the dynamic impact of economic liberalization (financial and trade liberalization) on ASEAN’s economic growth and to assess the possibility of the existence of convergence club between ASEAN and its RCEP counterparts. Using the annual data covering the period of 1994 to 2014, the analysis is based on the Pooled Mean Group (PMG) estimations for liberalization analysis while the Phillips and Sul (2007) methodology is used to assess the economic convergence clubs. The empirical evidence suggests that both trade and financial liberalization play a significant role in ASEAN’s economic growth. For convergence in RCEP, full sample find an absence of homogenous convergence; as a result, four club convergences are formed. The result highlights the importance of trade and financial liberalization in enhancing economic growth of ASEAN and implies that strong commitments in continuation of liberalization and integration policies are recommended to promote a sustained economic growth.